PENGARUH GOOD CORPORATE GOVERNANCE DAN PENGENDALIAN INTERNAL TERHADAP PENCEGAHAN FRAUD: Studi Kasus pada Pemerintah Kota Cimahi - Makarimovic, Awwab; Setyanto, Eko; Handayani, Rini (Jurnal Ilmu Akuntansi, 2022)
This study was conducted to determine how much influence good corporate governance and internal control have on fraud prevention either partially or simultaneously in the Cimahi City Government. The phenomenon in the Cimahi City Government is that there are still frauds committed by the Mayor of Cimahi for the terms of office 2002-2012, 2012-2017 and in 2020 and using the saturated sampling method or census with a population of 71 respondents from BPKAD, BAPPEDA, and Cimahi City Inspectorate, by distributing questionnaires. Hypothesis testing using multiple linear regression and tested using SPSS version 25. The partial test results in this study state that there is a significant positive effect between the variables of Good Corporate Governance (X1) on Fraud Prevention (Y). This can be seen from the value of > (5.463<1.99547). There is a significant positive effect between the Control variables Internal (X2) towards Fraud Prevention (Y). The value of > (5.355<1.99547). The test results simultaneously state that Good Corporate Governance (X1) and Internal Control (X2) jointly affect Fraud Prevention (Y). This is indicated by the value of > which is 79.907 > 3.13 and a significance level of 0.000 <0.05. For testing the determination that the value of R Square is 0.702 or 70%. This means that Good Corporate Governance (X1) and Internal Control (X2) together affect Fraud Prevention (Y) by 70% and the remaining 30% is influenced by other variables.